2016
DOI: 10.1080/02640414.2016.1159716
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex and limb dominance on lower extremity joint mechanics during unilateral land-and-cut manoeuvres

Abstract: Limb dominance theory suggests that females tend to be more one-leg dominant and exhibit greater kinematic and kinetic leg asymmetries than their male counterparts, contributing to the increased risk of anterior cruciate ligament injury among female athletes. Thus, the purpose of this study was to examine the influences of sex and limb dominance on lower extremity joint mechanics during unilateral land-and-cut manoeuvres. Twenty-one women and 21 men completed land-and-cut manoeuvres on their dominant limb as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…To control these large landing GRFs, females used greater hip flexion moment compared to males. This strategy is a noted sex dimorphism for females during landing [2123], and has been attributed to poor neuromuscular control at the hip [8,20,44] and disproportionate strength of the hip abductor and knee flexor muscles [8,44]. Neuromuscular training has been shown to reduce females’ knee injury risk [16,44] by focusing on increasing hip abduction strength [45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To control these large landing GRFs, females used greater hip flexion moment compared to males. This strategy is a noted sex dimorphism for females during landing [2123], and has been attributed to poor neuromuscular control at the hip [8,20,44] and disproportionate strength of the hip abductor and knee flexor muscles [8,44]. Neuromuscular training has been shown to reduce females’ knee injury risk [16,44] by focusing on increasing hip abduction strength [45].…”
Section: Discussionmentioning
confidence: 99%
“…While the existing literature is inconclusive on limb differences during landing [23,24], with the addition of body borne load participants may rely more on the stronger dominant limb [46,47] to safely attenuate the impact forces for both normal and flexed landings [16]. Participants’ dominant limb exhibited greater peak vertical (NL: 12%, FL: 8%) and frontal (NL: 13%, FL: 7%) GRFs and peak knee flexion moment than the non-dominant limb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The few studies comparing the I-vGRF of males and females dropping from relative height (RH) have found that there are no sex differences during unilateral landings [ 17 , 18 ]. However, these studies were only focused on one RH (100% jump height of the countermovement jump).…”
Section: Introductionmentioning
confidence: 99%